2019
DOI: 10.3390/medicina55080457
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Emergency Department Unscheduled Return Visits

Abstract: Background and Objectives: This study aims to identify reasons for unscheduled return visits (URVs), and risk factors for diagnostic errors leading to URVs, with comparisons to data from a similar study conducted in the same institution 9 years ago. Materials and Methods: This retrospective study included adult patients who attended the emergency department (ED) of a tertiary hospital in Singapore between January 2014 and June 2014, with re-attendance within 72 h for the same or similar complaint. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Abdominal pain was the focus of a research study in Poland (Kacprzyk, 2020), where diagnosis and management of abdominal pain was reported as a challenge with 10.88% of patients returning as a URV. Abdominal pain was the most common clinical complaint in the Singapore study (Soh et al , 2019). Another clinical condition of concern as a risk factor are neurological complaints which in one study comprised 12.5% of the total URV within 72 h (Schouten, 2019).…”
Section: Discordant Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal pain was the focus of a research study in Poland (Kacprzyk, 2020), where diagnosis and management of abdominal pain was reported as a challenge with 10.88% of patients returning as a URV. Abdominal pain was the most common clinical complaint in the Singapore study (Soh et al , 2019). Another clinical condition of concern as a risk factor are neurological complaints which in one study comprised 12.5% of the total URV within 72 h (Schouten, 2019).…”
Section: Discordant Outcomesmentioning
confidence: 99%
“…An alternative way of understanding the high levels of URV across England is to review the data on capacity and demand in ED where there has been unprecedented demand on emergency departments in England outstripping the capacity of the ED service (Baker, 2019). URV are a global problem, however, there are wide inconsistencies in the literature as to how URV are defined in adults attending the emergency department, with URV rates in England, within seven days, between 0.4% and 43% (Trivedy and Cooke, 2015); Canada (Hayward et al , 2018) and Singapore (Soh et al , 2019) defining URV as 72 h and Hong Kong within 48 h (Ng and Chung, 2003). Much of the literature focuses on a 72 h URV period with the Royal College of Emergency Medicine recommending that a future quality indicator for ED should include URV within 72 h to an English ED to be seen by a consultant or a senior decision maker (RCEM, 2019) There is a suggestion that by studying the attendance at the index visit to the emergency department, patients who are at high risk for a URV may be identifiable prior to this occurring (Hayward et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive exploration and verification of the characteristics of 72-h URVs have been conducted in numerous studies, with comorbidity assessment, such as the Charlson Comorbidity Index (CCI), being utilized to predict the 30-day mortality rate for elderly patients visiting the emergency department (ED) [ 14 , 15 ]. Additionally, a higher CCI score has been associated with admission, transfer, or death in the ED [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for ED revisits, abdominal pain is the most common chief complaint as well [ 12 16 ]. Crystal et al demonstrated that abdominal pain accounted for the highest proportion of URVs (22.2%), followed by fever (21.0%) and other gastrointestinal symptoms (19.7%) [ 17 ]. To stratify the risk of abdominal pain is difficult because even symptoms and signs of acute abdomen could be atypical and nonspecific in the initial phase [ 5 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite improvements in knowledge and techniques over time, there was a trivial decrease of the URV rate in emergency medical care. Kuan investigated the URV rate over a 9-year period and revealed that the URV rate only declined from 25.1 to 22.2% [ 17 ]. Hence, abdominal-pain-related URVs remain a leading challenge in the ED setting.…”
Section: Introductionmentioning
confidence: 99%